THE EFFECTIVENESS OF WEB BLOG MEDIA TO TEACH READING AT FIRST SEMESTER OF STKIP HAMZANWADI SELONG IN THE ACADEMIC YEAR 2011-2012 - Muhammad Husnu (Universitas Hamzanwadi, 2012)
Reading is an extremely effective means of extending our command of language, so it has a crucial place in classroom in which language learning is a central purpose. In teaching reading, a media is needed; it can make the students motivating and interesting. One of the media used was blog. Blog media can be adopted in any classroom to encourage active learning among students. The problems stated in this study are what extent that blog as teaching media effective in teaching reading at first semester of STKIP Hamzanwadi Selong in the academic years 2011-2012? and how to use blog as teaching media in teaching reading at first semester of STKIP Hamzanwadi Selong in the academic years 2011-2012? This is a classroom action research. In this study, there were three cycle must be conducted with total of students were 35 students as a research subject. The writer used an observation of students activity and a test to evaluate the students’ learning result in reading comprehension in form of multiple choices test that consisted of 20 items which each items consisted of four options After collecting and calculating the data, the researcher found that the successful percentage of each cycles were: for observation of students learning result got at cycle I (2,7), cycle II (4,6), cycle III (8,0) and the result of students learning evaluation got at cycle I (54,28%), cycle II (68,57%), cycle III (91,42%). Based on the result of data collection, using blog as a media in teaching reading comprehension was more effective than students who were taught by conventional strategy. Key Words: Blog as a media and Teaching Reading